ORAL LITERARY MORAL VALUE ANDAI-ANDAI â€œBESAN PUYUHâ€ IN THE SUB- DISTRICT KIKIM LAHAT REGENCY - Wardiah, Dessy (Jurnal Dosen Universitas PGRI Palembang)
AbstractThe issues raised in this research is how the moral value in oral literature Andai-Andai?Besan Puyuh? in sub-district of Kikim Lahat regency. The method used in this research descriptive qualitative method. The data in this research were from oral literature transcriptions Andai-Andai?Besan Puyuh? in sub-District of Kikim Lahat regency. Sources of data obtained from two persons were Mr. Bahari Gena (81 years old) and Mrs. Yahima (78years old). The data collection techniques used were recording, observation and interviews. Data were analyzed using content analysis techniques. The Results of the research showed that the oral literature of Andai-Andai?Besan Puyuh? is a part of fables category, which have moral value massage of individual include; the nature of sacrifice, trust in keeping promises and understand the return the favor. Apart from that, the message of social moralvalues describe through the nature of caring, the attitude of cooperation, helpfulness, compassion, harmony, mutual giving, and caring about others. Index Terms: Moral Values, Oral Literature, Andai-Andai?Besan Puyuh